RELATIONS BETWEEN THE USE OF ACTIVITY BASED COSTING SYSTEM AND CONTINGENCY FACTORS: EVIDENCE FROM BRAZILIAN NGOS - Oliveira, Alan Santos de; Arruda, Lorena de Souza; Callado, Antônio André Cunha; Callado, Aldo Leonardo Cunha (Advances in Scientific and Applied Accounting, 2020)
In the context of Non-Governmental Organizations, management control practices cannot simply be replicated, because due to their specificities as well as internal and external environmental contingency factors, these organizations need to make adjustments and adaptations so that these same practices can be useful for the process of decision making. This paper aims to analyze how significant are the relations between the use of the ABC system and contingency factors among Brazilian Nongovernmental Organizations (NGOs). To reach this objective, a descriptive, exploratory and quantitative survey was carried out. The universe of this research was composed by all NGOs listed in the Brazilian Association of Non-governmental Organizations (ABONG). All of them were invited to participate in the survey and 43 agreed to provide information regarding the use of the ABC system and six groups of contingency factors. Data collection was performed through questionnaires sent by correspondence. All variables were operated on a six-level ordinal scale. The statistical technique used to analyze the significance of the relations tested was Kruskall-Wallis test. The results indicated evidence of statistically significant relationships between the use of the ABC method system and contingency factors related to strategy, structure, technology and culture.